Work-Time, Male-Breadwinning and the Division of Domestic Labour: Male Part-Time and Full-Time Workers in Unsettled Times. (February 2022) - Warren, Tracey
The majority of male workers spend full-time hours in the labour market while part-time employment is heavily female dominated. A decade of economic unrest in the UK following the recession of 2008–2009 was accompanied by a considerable expansion in the numbers of men working part-time. Growing male part-time employment is a significant phenomenon, with potential for narrowing gender inequalities in ways of working, inside and outside the home. Applying a gendered lens to men's working lives, the article focuses upon the ramifications of this growing male work-time diversity. Unsettled times can create the circumstances for opening up acceptable behaviours, for 'undoing' gender roles. The financial circumstances of male part- and full-timers, and men's engagement in unpaid domestic work, are compared. Part-time jobs are associated with more financial hardship than are full-time, but they offer up the potential for narrowing gender inequality in the sharing of core domestic work tasks.